A Comparative Analysis Between BPMN and ISO 19440 Modeling Language Constructs - Rochetti, Angela Teresa [UNESP]; Campos, Renato de [UNESP]; Naas, I; Vendrametto, O.; Reis, J. M.; Goncalves, R. F.; Silva, M. T.; VonCieminski, G.; Kiritsis, D. (Springer, 2016)
Enterprise modeling is a tool that can be used for simple objectives, such as understanding how a part of the enterprise works, to more complex objectives, such as information flow for the computerized systems, or knowledge storage in an organization. There are several languages proposed for enterprise modeling, such as BPMN, CIMOSA and UML. They have different characteristics, advantages and disadvantages. This paper presents a comparison in relation to representation capacity between the ISO 19440 language constructs and the BPMN notation based on their constructors and icons. The analysis shows that BPMN has less representation capacity, showing differences between one language for modeling various aspects in an enterprise (ISO 19440) and a notation (BPMN) which focuses on process modeling and has few constructs for representing other aspects such as an enterprise's resources and organization.
Keywords: Process modeling; Enterprise; Modeling; BPMN; ISO 19440